THU0478 IS NEUROPATHIC PAIN IN INFLAMMATORY RHEUMATIC DISORDERS AN UNDERESTIMATED PROBLEM? RESULTS FROM THE GERMAN PAINDETECT DATABASE. (2nd June 2020) - Sewerin, P.; Freynhagen, R.; Tölle, T.; Hammer, M.; Baerwald, C.; Walter, J.; Schröder, R.; Schneider, M.; Baron, R.
Abstract : Background: The aim of the study was to investigate the impact and relevance of neuropathic pain in inflammatory rheumatic disorders (IRD) and osteoarthritis (OA). Objectives: Pain is one of the main symptoms in patients with IRD and OA. To enhance a mechanistic based treatment of pain the differentiation between nociceptive and neuropathic pain via screening tools (e.g. painDETECT questionaire) might possibly be helpful. The goal of the study was to investigate (1) if neuropathic pain is a significant burden for patients with IRD and (2) if pain patterns differs from degenerative joint diseases such as OA in over 9.000 patients in each group. Methods: painDETECT is a questionnaire that has been evaluated and used in numerous clinical trials to detect neuropathic pain in various diseases. The collected data is centrally managed and evaluated. In total (end of 2019) 395.984 patients have been documented. Out of the painDETECT database 9256 patients with IRD and 9436 patients with OA were extracted, analyzed and compared on their neuropathic pain pattern (screening was performed using the painDETECT-questionaire., PDQ). Secondary parameters were: intensity of pain, functional status, depression, chronicity and sleep disorder. Patients had been recruited from general practitioners (GPs), Rheumatologists, Orthopedics and Neurologists from 862 office-based physicians into the painDETECT-database. This project is an open label registry study in Germany. Results: The median PDQ-score of patients with inflammatory rheumatic disorders adds up to 14, 2 (1-38) and of OA patients to 13, 8. 28.7% of inflammatory rheumatic disorders and 27.2% of OA-patients showed signs for neuropathic pain by positive PDQ. The difference was according to this high patient numbers statistically significant (P=0.0015). VAS-Score, Depressions-Score, Chronicity -Score and Functional -Score showed no clinically relevant differences between these two groups. Conclusion: Nearly one third of patients with IRD as well as patients with OA showed neuropathic pain components by using PDQ. Despite increasingly better disease control through more effective therapies, pain still remains a major burden for many patients and has a profound impact on their quality of life. The present data indicate a surprisingly high symptoms of neuropathic pain even in IRD patients and should be considered in the management of our patients. A new documentation system for Rheumatologists (RheumaAssist) could help to address these questions. Percentage of PDQ-categories (negative/unclear/positive) for patients with inflammatory rheumatic disorders (IRD) or Arthrosis (OA) Acknowledgments: This investigation was supported within a grant of Pfizer Deutschland GmbH. Disclosure of Interests: Philipp Sewerin Grant/research support from: AbbVie Deutschland GmbH & Co. KG Bristol-Myers Squibb Celgene GmbH Lilly Deutschland GmbH Novartis Pharma GmbH Pfizer Deutschland GmbH Rheumazentrum Rhein-Ruhr, Consultant of: AMGEN GmbH AbbVie Deutschland GmbH & Co. KG Biogen GmbHBristol-Myers Squibb Celgene GmbH Chugai Pharma arketing Ltd. / Chugai Europe GmbHHexal Pharma Janssen-CilagGmbH Johnson & Johnson Deutschland GmbHLilly Deutschland GmbH / Lilly Europe / Lilly Global Novartis Pharma GmbH Pfizer Deutschland GmbH Roche Pharma Rheumazentrum Rhein-Ruhr Sanofi-Genzyme Deutschland GmbH Swedish Orphan Biovitrum GmbH UCB Pharma GmbH, Speakers bureau: AMGEN GmbH AbbVie Deutschland GmbH & Co. KG Biogen GmbHBristol-Myers Squibb Celgene GmbH Chugai Pharma arketing Ltd. / Chugai Europe GmbHHexal Pharma Janssen-CilagGmbH Johnson & Johnson Deutschland GmbHLilly Deutschland GmbH / Lilly Europe / Lilly Global Novartis Pharma GmbH Pfizer Deutschland GmbH Roche Pharma Rheumazentrum Rhein-Ruhr Sanofi-Genzyme Deutschland GmbH Swedish Orphan Biovitrum GmbH UCB Pharma GmbH, Rainer Freynhagen Consultant of: AOP Orphan Pharma, Grünenthal, Lilly, Merck, Mitsubishi Tanabe Pharma, Pfizer, Scilex Pharmaceutics, Speakers bureau: AOP Orphan Pharma, Grünenthal, Lilly, Merck, Mitsubishi Tanabe Pharma, Pfizer, Scilex Pharmaceutics, Thomas Tölle Consultant of: AOP Orphan, Almiral Hermal, Bionest Partners, Benkitt Renkiser, Grünenthal, Hexal, Indivior, Kaia Health, Lilly, Medscape Mundipharma, MSD, Novartis, Pfizer, Recordati Pharma, Sanofi-Aventis, and TAD Pharma, Speakers bureau: AOP Orphan, Almiral Hermal, Bionest Partners, Benkitt Renkiser, Grünenthal, Hexal, Indivior, Kaia Health, Lilly, Medscape Mundipharma, MSD, Novartis, Pfizer, Recordati Pharma, Sanofi-Aventis, and TAD Pharma, Michael Hammer Consultant of: Abbvie, Pfizer, Medac and Janssen, Speakers bureau: Abbvie, Pfizer, Medac and Janssen, Christoph Baerwald Consultant of: CGB received speaker or consulting fees from AbbVie, Paid instructor for: CGB received speaker or consulting fees from AbbVie, Speakers bureau: CGB received speaker or consulting fees from AbbVie, Jochen Walter Consultant of: Pfizer, Speakers bureau: AbbVie, Frauenhofer Institut, Gilead, Janssen-Cilag, Medac, Novartis, Pfizer, Ralf Schröder Shareholder of: Pfizer Pharma GmbH, Employee of: Pfizer Pharma GmbH, Matthias Schneider Grant/research support from: GSK, UCB, Abbvie, Consultant of: Abbvie, Alexion, Astra Zeneca, BMS, Boehringer Ingelheim, Gilead, Lilly, Sanofi, UCB, Speakers bureau: Abbvie, Astra Zeneca, BMS, Chugai, GSK, Lilly, Pfizer, Sanofi, Ralf Baron Consultant of: RB received speaker or consulting fees from AbbVie, Paid instructor for: RB received speaker or consulting fees from AbbVie, Speakers bureau: RB received speaker or consulting fees from AbbVie